Comparison of flywheel versus traditional resistance training in elite academy male Rugby union players - Murton, J.; Eager, R.; Drury, B. (Research in Sports Medicine, 2021)
This study investigated the effects of flywheel inertia training (FIT) vs traditional resistance training (TRT) over four weeks in academy male rugby union (RU) players. Sixteen elite male academy RU players (age = 18.0 ± 1.0 years, body mass = 93.0 ± 13.1 kg) were allocated into either FIT (n = 8) or TRT (n = 8) groups. Pre and post measures of countermovement jump (CMJ), squat jump (SJ) and drop jump (DJ) were completed. Relative peak force (PF), relative peak power (PP) and jump height (H) were measured for CMJ and SJ with reactive strength index measured for the DJ. Both groups showed improvements in all measures, except for SJ peak power, following TRT. Within-group analysis showed significant increases following TRT in CMJ-H (2.79 cm, 90% CI = -0.70, 4.89 cm; p = 0.002; ES = 0.51) and SJ-H (3.68 cm, 90% CI = 1.25, 6.11 cm; p = 0.002; ES = 0.88) with a significant improvement following FIT for CMJ-PP (1.96Wkg-1, 90% CI = -0.89, 4.80 Wkg-1; p = 0.022; ES = 0.55). No significant between-group differences (p > 0.05) were evident. These findings suggest both FIT and TRT are effective for developing lower-body strength and power qualities in male academy RU players.